Distribution patterns of antioxidants in the organs of anadromous fish Tenualosa ilisha (Hamilton, 1822)—a profiling in different age groups for future application in anti-aging - Chakraborty, Hena; Das, Basanta Kumar; Chakraborty, Nabanita; Sahoo, Amiya Kumar; Maity, Joydev (Frontiers in Marine Science, 2024)
The present study focuses on the antioxidant levels in various organs of Hilsa fish, both male and female, with a weight range of 50g to 780g collected from the Hooghly River in the lower Gangetic plain. The study utilized commercially available free radicals such as viz., 2, 2'-azinobis-[3-ethyl-benzothiazoline-6-sulfonic acid] (ABTS) and ferric reducing antioxidant potential (FRAP) to measure the scavenging activity. The results indicated that female Hilsa fish possess higher levels of antioxidants (93.79±0.26) compared to male counterparts (84.50±0.65) in all organs, with levels increasing proportionally with weight. Interestingly, in males, the serum antioxidant profile was higher in the lower weight group (50-100g), while in females, the highest antioxidant activity was observed in the weight range of 300g-400g. The present study was attempted for the first time the first attempt to characterise the antioxidant distribution pattern in the different organs of Hilsa. These findings suggest promising Hilsa fish organs, including serum, contain high levels of antioxidants that could significantly be benefit human nutrition and potentially will contribute to anti-ageing effects by adding incorporating Hilsa to their diet which needs further clinical study.